THE NARRATIVE OF THE TEACHER IN THE CONTEXT OF MUSIC EDUCATION - Venslovaitė, Vita (Acta Paedagogica Vilnensia, 2014)
In this article, the essential features of the narrative – multimeaning and roughness – are highlighted, and their importance in the educational process is shown. The narrative is examined based on the paradigms of the postmodern and phenomenological philosophies. In the postmodern concept of storytelling, the narrative is interpreted not only in the historical context, but is highlighted also as a verbal act. The base of the research of the narrative is the belief that stories give meaning to peoples’ lives and therefore can be processed as data. Also, it is analyzed how the narrative, from being a phenomenological perspective, gains a status of the method that gives a possibility of self-expression to a person, based on individual experience.The phenomenological empirical research has shown, that the teacher’s narrative, which is composed from a story (or from a metaphor), is a spur for students’ aesthetical perception. It dehisces in many different forms and spans over the past, the present, and the future. The narrative shows itself being multimeaningful, because it performs the functions of information, communication, intercommunication, and musical expression.Interviews with teachers and the observed lessons have revealed the teachers’ narrative, presented as a graphic story of experience (or a metaphor), to be an important part of musical education in each individual lesson. On the one hand, the teacher directs the student to a desired object of perception with his narrative, but, on the other hand, through the interpretations of one’s imagination, the teacher opens up multiple choices for a student to accept the meaning in his own way.
Keywords: narrative; postmodernism; phenomenology; narrative pedagogy; music education